2016
DOI: 10.1016/j.jtusci.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of silver nanoparticles using a pod extract ofCola nitida: Antibacterial and antioxidant activities and application as a paint additive

Abstract: This work reports the biogenic synthesis of silver nanoparticles (AgNPs) using the pod extract of Cola nitida, the evaluation of their antibacterial and antioxidant activities, and their application as an antimicrobial additive in paint. The AgNPs were characterized with UV-Vis spectroscopy, Fourier-transform infrared (FTIR) spectroscopy, and transmission electron microscopy (TEM). The AgNP solution was dark brown with a maximum absorbance occurring at 431.5 nm. The FTIR spectrum showed strong peaks at 3336.85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(93 citation statements)
references
References 56 publications
8
85
0
Order By: Relevance
“…The AgNPs used in this study have been found to be highly potent, with higher DPPH scavenging activities than quercetin and b-carotene (Lateef et al 2016g). Antioxidant activities of leaf extracts of A. caudatus witnessed reduction with increase in the concentration of AgNPs.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The AgNPs used in this study have been found to be highly potent, with higher DPPH scavenging activities than quercetin and b-carotene (Lateef et al 2016g). Antioxidant activities of leaf extracts of A. caudatus witnessed reduction with increase in the concentration of AgNPs.…”
Section: Discussionmentioning
confidence: 77%
“…AgNPs used in this study were biologically synthesized using the pod extract of C. nitida as previously reported by Lateef et al (2016g). The scheme of the synthesis is shown in Fig.…”
Section: Biosynthesis and Characterization Of Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the fabricated AgCl‐NPs had approximately 5.6‐fold lower antioxidant activity than the ascorbic acid standard, they might be used as a synergetic antioxidant agent. The results of DPPH scavenging activity indicated that biofabricated AgCl‐NPs in this study had antioxidant activity like other biofabricated Ag/AgCl‐NPs such as nanoparticles fabricated using M. citrifolia leaf extract , C. papya peel extract , pod extract of Cola nitida and Chenopodium murale leaf extract .…”
Section: Resultsmentioning
confidence: 68%
“…The increase in the absorbance of the reaction mixture indicates stronger reducing power. The free radical scavenging activity of SNPs attributes to functional groups of bio-reductant molecules adhered to the surface of nanoparticles 35 .…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%